Becoming Atheist: Humanism and the Secular West - Brown, Callum G. (Bloomsbury Publishing PLC, 2017)
Cover -- Contents -- List of Tables -- Preface -- Acknowledgements -- 1 Introduction -- One by one -- Imagining secularization -- Of numbers and cultures -- What is the secular? -- Researching the little imagined atheist -- 2 Narratives of Belief and Unbelief -- Oral history and religion -- The Christian self -- The fortified religious self -- Race and ethnicity -- The feminist liberation narrative -- Secularization narratives -- Conclusion -- 3 The Atheist Child -- Religion and child development -- Religious childhoods -- Growing up faithless -- Converting the family -- Childhood disaffection -- The child atheist -- 'What colour is life?' The youthful maturation of atheism -- 4 The Silent and Indifferent Atheist -- Approaching indifference -- The silence of non-belief -- The character of indifference -- Leaving indifference -- 5 Women, Feminism and Becoming Faithless -- Narrating the gendered non-religious self -- 'It's really rotten being a woman sometimes': Trauma and the family -- 'To be a person': Living feminism and the loss of religion -- The New Age and 'absolutely no god thing' -- Flying through the air -- 6 Men, Reason and Radicalism -- Absences and silences -- Reason - the male prerogative? -- Leaving the priesthood -- Reading -- Deserting dysfunction -- Trauma -- Being an atheist man -- 7 Atheism and Ethnicity -- The African American -- The Jews -- The Muslim -- The Hindus -- The whites -- It's not for me to judge humanism -- 8 The Humanist Condition -- After religion -- The hesitant atheist -- Finding the humanist condition -- Becoming atheist with a heart -- The transition generation -- Notes -- Sources -- Index.